Pretreatment of Ascorbic Acid Inhibits MPTP-Induced Astrocytic Oxidative Stress through Suppressing NF-κB Signaling - Xiaokang Zeng; Kai Xu; Ji Wang; Yunqi Xu; Shaogang Qu (Neural Plasticity)
Astrocytes are a major constituent of the central nervous system (CNS). Astrocytic oxidative stress contributes to the development of Parkinson’s disease (PD). Maintaining production of antioxidant and detoxification of reactive oxygen and nitrogen species (ROS/RNS) in astrocytes is critical to prevent PD. Study has illuminated that ascorbic acid (AA) stimulates dopamine synthesis and expression of tyrosine hydroxylase in human neuroblastoma cells. However, the role and regulatory mechanisms of AA on detoxification of astrocytes are still unclear. The purpose of our study is in-depth study of the regulatory mechanism of AA on detoxification of astrocytes. We found that AA pretreatment decreased the expression of ROS and inducible nitric oxide synthase (iNOS) in MPP+-treated astrocytes. In contrast, the expression levels of antioxidative substances—including superoxide dismutase (SOD), glutathione (GSH), and glutamate-cysteine ligase modifier (GCLM) subunit—were upregulated after AA pretreatment in MPP+-treated astrocytes. However, inhibition of NF-κB prevented such AA induced increases in antioxidative substances following MPP+ treatment in astrocytes, suggesting that AA improved antioxidative function of astrocytes through inhibiting NF-κB-mediated oxidative stress. Furthermore, in vivo studies revealed that AA preadministration also suppressed NF-κB and upregulated the expression levels of antioxidative substances in the midbrain of MPTP-treated mice. Additionally, pretreatment of AA alleviated MPTP-induced PD-like pathology in mice. Taken together, our results demonstrate that preadministration of AA improves the antioxidative function of astrocytes through suppressing NF-κB signaling, following alleviated the pathogenesis of PD which induced by MPTP. Hence, our findings elucidate a novel protective mechanism of AA in astrocytes.